LAND SUITABILITY EVALUATION FOR DEVELOPING LEMBAH PALU SHALLOT VARIETY CULTIVATION IN THE UPPER PART OF BULUBASEH WATERSHED DONGGALA DISTRICT - Danang Widjajanto; Uswah Hasanah; Imam Wahyudi (Journal of Agroecology, 2015)
Lembah Palu shallot variety is a high priority commodity in Palu Valley. However, developing this commodity has faced constraints in its management. Therefore, it is important to conduct study on land suitability evaluation for Lembah Palu shallot variety cultivation based on characteristics which are environmentally specific for growing the Lembah Palu shallot variety. The aim of the research was to evaluate quantitatively and qualitatively the land suitability of Bulubaseh watershed for developing Lembah Palu shallot variety cultivation in Donggala district. Soil survey conducted in the watershed was using stratified random method approach. The stratification was determined based on the research land units obtained by overlaying different types of maps including land use, topography and soil type maps resulting in nine land units. Soil samples from each land unit were randomly taken. The quantitative land suitability evaluation was done through analysis of farming financial suitability, while the qualitative land suitability was approached parametrically. The research results showed that generally the climate of the watershed was moderately suitable (S2) and about 884.86 ha or 57.3% of the total land area of Bulubaseh watershed was classified as marginally suitable (S3) with climate, land slope, solum depth and base saturation were the main constraints. The result of the quantitative land suitability indicated that financially Lembah Palu shallot variety is suitable to be developed as a farming system for the farmers in Bulubaseh watershed, Donggala district.